1993
DOI: 10.1364/ol.18.000747
|View full text |Cite
|
Sign up to set email alerts
|

Double-pulse technique for optical emission spectroscopy of ablation plasmas of samples in liquids

Abstract: Sharp atomic and ionic line spectra of excimer-laser-induced ablation plasmas of samples in liquids were observed. A new double-pulse technique employing quartz fibers facilitates spectral analysis of samples in liquids in which spectral lines normally are strongly broadened and quenched. The first pulse generates a cavitation bubble on the sample surface, which provides a gaseous environment for optical emission spectroscopy on the ablation plasma induced by a second pulse fired into the bubble.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 9 publications
1
53
0
Order By: Relevance
“…This behavior was reported by Nyga et al [91] during the ablation of samples submerged in water (Fig. 16).…”
Section: Ambientsupporting
confidence: 83%
See 2 more Smart Citations
“…This behavior was reported by Nyga et al [91] during the ablation of samples submerged in water (Fig. 16).…”
Section: Ambientsupporting
confidence: 83%
“…Plasma properties have been studied in different gases [81,[85][86][87][88][89], as a function of pressure [85,90], even in liquids [91][92][93]. The ambient gas either helps or prevents the coupling of laser energy into the plasma.…”
Section: Ambientmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions within the optically dense plasmas generated underwater are far from ideal for spectroscopy (Sakka et al, 2002;Pichahchy et al, 1997). In order to overcome this problem, most studies concerning underwater LIBS have used a double-pulse technique (Nyga and Neu, 1993;De Giacomo et al, 2005;Lazic et al, 2005Lazic et al, , 2007, where a first pulse is used to create a cavity into which a second pulse is delivered, allowing mechanisms similar to LIBS in a gas to take place. However, several studies have reported that this method is sensitive to external pressure, with pressures of just a few MPa, corresponding to depths of a few hundreds of meters, having a significant detrimental effect on the analytical value of the signals obtained Michel and Chave, 2008b;De Giacomo et al, 2011;Takahashi et al, 2013).…”
Section: Underwater Libs At High Pressurementioning
confidence: 99%
“…Since then a more thorough understanding of the atomic processes occurring in laser produced plasmas together with technical improvements in spectroscopic instrumentation has allowed considerable improvement in the performance of LIBS systems [2,3]. LIBS is made possible because of the high power densities, in excess of 10 W cm\, that may be produced by a focused laser beam.…”
Section: Introductionmentioning
confidence: 99%